Mergers and the Competitive Process - John Baldwin; Paul Gorecki (Queen's University, Department of Economics, 1990)
This paper uses a longitudinal data base of establishments and firms taken from the Canadian Census of Manufactures to measure the intensity of mergers and to compare them to other change that leads to firm turnover. The importance of mergers is placed in the context of the plant and firm turnover process by comparing the amount of each merger type to alternate forms of expansion. Horizontal merger activity is compared to the creation of new plants by continuing firms. Entry by diversification is compared to entry by plant birth. The paper then investigates post-merger success by examining market share, productivity, and profitability changes. When the extent to which acquired plants are subsequently divested is used to evaluate success, this divestiture process is compare to the exit rate of newly built plants. When changes in post-merger market share are examined, a regression is used to examine whether merged plants act any differently than other plants. When post merger productivity and profitability changes are examined, they are compared to what is happening to other plants in the same industry. The paper finds that the merger process contributes an important part of firm turnover and that the merger process improves productivity and profitability.
Keywords: 330; merger; firm turnover; diversification; productivity; profitability; market share